ETIOLOGY AND CLINICAL CHARACTERISTICS OF MACULAR EDEMA IN PATIENTS WITH FAMILIAL EXUDATIVE VITREORETINOPATHY. Issue 7 (July 2020) - Rao, Prethy; Lertjirachai, Itsara; Yonekawa, Yoshihiro; Hasbrook, Madeline; Thomas, Benjamin J.; Wood, Edward H.; Mehta, Neesurg; Mane, Greta; Drenser, Kimberly A.; Trese, Michael T.; Capone, Antonio
Abstract : Purpose: To describe the etiology and clinical characteristics of macular edema (ME) in patients with familial exudative vitreoretinopathy. Methods: Observational, retrospective case series of 30 patients (34 eyes) with ME and familial exudative vitreoretinopathy who underwent spectral-domain optical coherence tomography imaging between 2009 and 2016. Baseline and follow-up optical coherence tomographies were correlated with color fundus photography and fluorescein angiography. Results: The average age was 20.6 years (6.6–68.7). Eighteen eyes exhibited cystoid ME (52.9%), 14 noncystoid ME (41.2%), and 2 eyes (5.9%) with both. Macular edema was foveal in 52.9% (n = 18). Eighteen of 24 eyes (64.3%) with an available fluorescein angiography showed leakage from ME. The most common structural feature was posterior hyaloidal organization/contraction (n = 15). Sixteen eyes were treated with topical or intravitreal steroids (n = 6), intravitreal anti–vascular endothelial growth factor (n = 3), or pars plana vitrectomy with membrane stripping (n = 7). There was no difference between mean preoperative and postoperative LogMAR visual acuity (0.63 [20/85] vs. 0.87 [20/148], P = 0.35) after vitrectomy despite a statistical improvement in the mean central foveal thickness (596 mm 3 vs. 303 mm 3, P = 0.04). Conclusion: Macular edema in familial exudative vitreoretinopathy occurs most commonly because of traction. Vitrectomy is effective for relieving tractional forces with anatomical improvement. Abstract : We present the clinical characteristics of macular edema in familial exudative vitreoretinopathy eyes. Most eyes demonstrate posterior hyaloidal organization/contraction associated with macular edema and vascular leakage on fluorescein angiography. Posterior hyaloidal organization–related edema may benefit from vitrectomy with membrane peeling.